2020
DOI: 10.1177/1550147720928897
|View full text |Cite
|
Sign up to set email alerts
|

Predictive analytics framework for accurate estimation of child mortality rates for Internet of Things enabled smart healthcare systems

Abstract: Globally, under-five child mortality is a substantial health problem. In developing countries, reducing child mortality and improving child health are the key priorities in health sectors. Despite the significant reduction in deaths of under-five children globally, developing countries are still struggling to maintain an acceptable mortality rate. Globally, the death rate of under-five children is 41 per 1000 live births. However, the death rate of children in developing nations like Pakistan and Ethiopia per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Various studies also confirmed that these factors are crucial for under-five mortality [ 3 39 ]. From this study, we can confirm that the wealth index was one of the important factors for under-five mortality, which is in line with other studies [ 40 42 ].…”
Section: Discussionmentioning
confidence: 91%
“…Various studies also confirmed that these factors are crucial for under-five mortality [ 3 39 ]. From this study, we can confirm that the wealth index was one of the important factors for under-five mortality, which is in line with other studies [ 40 42 ].…”
Section: Discussionmentioning
confidence: 91%
“…is research [25] highlights the Internet of things enabled smart devices framework for accurate estimation of child mortality.…”
Section: Related Workmentioning
confidence: 99%
“…This technology includes machine learning (ML) and artificial intelligence (AI) integrated into the design and architecture of the entire system [31]. Some of the researches conducted in this area are blood pressure, heart-beat and glucose level [32][33][34], elderly healthcare [35], decentralized interoperable trust framework to enhances trustworthy factor (TF) estimation based on blockchain technology [36], estimation of under-five child mortality [37], and human activity recognition [38].…”
Section: Literature Reviewmentioning
confidence: 99%